2022
DOI: 10.1097/mcc.0000000000000959
|View full text |Cite
|
Sign up to set email alerts
|

Protein metabolism in critical illness

Abstract: Purpose of reviewCritically ill patients experience skeletal muscle wasting that may contribute to the profound functional deficits in those that survive the initial injury. Augmented protein delivery has the potential to attenuate muscle loss, yet the ability for dietary protein to improve patient outcomes is reliant on effective protein metabolism. This review will discuss the recent literature on protein delivery and digestion, amino acid absorption, and muscle protein synthesis (MPS) in critically ill adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
10
0
3
Order By: Relevance
“…A possible reason for these divergent findings may be that the protein intake was explored overall during the ICU stay, rather than focusing on the early phase as we did. Yet, early acute-illness-associated stress impairs protein–energy metabolism and its responsiveness to exogenous nutrients [ 52 , 53 ]. Koekkoek et al reported, in a recent retrospective study, a time-dependent association of protein intake with mortality: before day 3 in the ICU, a protein intake superior to 0.8 g/kg/day was associated with significantly higher 6-month mortality; after D3, a progressive increase protein provision was associated with an improvement in patients outcomes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for these divergent findings may be that the protein intake was explored overall during the ICU stay, rather than focusing on the early phase as we did. Yet, early acute-illness-associated stress impairs protein–energy metabolism and its responsiveness to exogenous nutrients [ 52 , 53 ]. Koekkoek et al reported, in a recent retrospective study, a time-dependent association of protein intake with mortality: before day 3 in the ICU, a protein intake superior to 0.8 g/kg/day was associated with significantly higher 6-month mortality; after D3, a progressive increase protein provision was associated with an improvement in patients outcomes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there has been increasing interest in the uptake and metabolism of dietary protein. Dietary protein has gained interest because of its potential to attenuate skeletal muscle wasting during critical illness and improve functional recovery of patients, though robust prospective evidence on this is still lacking [23]. Chapple et al [24 ▪▪ ] recently investigated protein digestion and absorption rates and the subsequent contribution of dietary protein to skeletal muscle protein synthesis in critical illness.…”
Section: Gastrointestinal Dysfunction and Nutrient Handlingmentioning
confidence: 99%
“…Several factors are known to increase net muscle protein breakdown including inflammation, oxidative stress, immobilization, and corticosteroid use [39,49,[55][56][57]. Critically ill patients also experience insulin resistance and anabolic resistance, which is a blunted anabolic response to amino acids characterized by failure to stimulate nutrient uptake and muscle protein synthesis and inhibit muscle protein breakdown [58,59]. Muscle atrophy frequently occurs in the ICU with the steepest rate of loss occurring within the first two weeks of ICU admission [60][61][62][63][64].…”
Section: The Need For Nutrition In Post-icu Rehabilitationmentioning
confidence: 99%